The public and private space in two cemeteries of the Puente Piedra district - Jara Chávez, Jelver Jhonatan (2019)
The study area chosen includes the Jardines del Buen Retiro cemetery and the Zapallal Municipal Cemetery, both in the Puente Piedra district and near the North Pan-American Highway. This ethnographic work is done to differentiate the space of common use in a private and public cemetery, taking into account the urban scales, the behavior of the visitors and the sociocultural relations that occur in both cemeteries.